Closure Scheme Analysis of 3 × 70 m Bearingless Integral Rigid Frame Bridge of Fuzhou Xiamen High-Speed Railway - Fangwen Weng; Xiangui Li (Advances in Civil Engineering)
The hydrodynamic problems associated with the construction of the sea-crossing bridge were proposed. The deep-water approach bridge on both sides of the main bridge of Fuzhou Xiamen high-speed railway adopts the bearingless prestressed concrete integral rigid frame bridge for the first time in the domestic railway bridge design. The rigid frame bridge applies the hanging basket cantilever construction, and there are several options for closure. Because the bridge structure system changes before and after closure, which will cause the redistribution of bridge internal force, the results of internal force redistribution will be different with the sequence and position of closure, and sometimes, there will be great changes. In order to select the optimal closure scheme, this article establishes the finite element model of the whole bridge and analyzes the whole construction process according to the working conditions and the mechanical state of the bridge before closure is obtained. Based on this state, eight closure schemes are analyzed and studied, which provides a sufficient mechanical basis for the determination of the final closure construction scheme.